Additions, Omissions, and Transformations in Institutional ‘Retellings’ of Domestic Violence - Lynn, Nicholas; Canning, Patricia (Language and Law / Linguagem e Direito, 2021)
In this paper we examine how UK police officers investigating domestic violence (DV) make a formal written case to Crown Prosecutors. Using rarely accessed ‘management guidance’ reports (MG3 forms) we analyses how police of-officers’ written contributions appeal to relevance and how they can ‘nudge’ prosecutors towards particular methods of case disposal, specifically, the ‘Simple Caution’.We propose that linguistic strategies can reduce the likelihood of convictions, and we raise serious concerns about the impact of police officers’ institutional ‘retellings’ in the pursuit of justice.